THE ROLE OF DIMENSIONS OF STRATEGIC RECOVERY OF SERVICE IN DEVELOPMENT OF EMPLOYEE LOYALTY (TYPICAL ASIASEL SERVICES) (World Bulletin of Management and Law, 2022)
Can the strategic recovery dimensions of the service be invested in developing the loyalty of the employees of a sample of the customers of Assail Communications, Al-Qadisiya branch in Iraq? Based on the previous literature, the survey tool was adopted to measure the availability of study variables in the services of the telecommunications company. Thus, 500 survey forms were distributed to selected clients working with the company, and 479 were retrieved for analysis, so the results showed that the dimensions of the strategic recovery of the service play an important role in developing the loyalty of the employees through the satisfaction of the customers. The study recommends that building positive customer relationships will improve customer loyalty toward the use of the company's services and build a positive reputation for them.